A morte da mulher na literatura alemã medieval : algumas considerações sobre a figura de Kriemhild em Das Nibelungenlied - Greenfield, John (2000)
The author attempts to interpret the relationship of the Kriemhild figure in 'Das Nibelungenlied' with the theme of death within the wider framework of Middle High German narrative poetry. The study concludes that in relation to this character and this theme, 'Das Nibelungenlied' has traits of both romance and heroic poetry.